A comparative study on the catalytic performance of different types of zeolites for biodiesel production. (15th October 2015) - Sun, Kaian; Lu, Jie; Ma, Lingling; Han, Ying; Fu, Zhongjun; Ding, Jincheng
Highlights: Different kinetic models were used to describe the esterification over zeolites. Al was verified to detect the leaching of active component of zeolite. The Cassie–Baxter model was used to study the effect of hydrophobic property. The Thiele modulus was used to investigate the effect of zeolite pore size. Microporous and micro-mesoporous zeolites were compared in biodiesel production. Abstract: Microporous zeolites (BEA type Beta zeolite and MFI type ZSM-5 zeolite) and micro-mesoporous zeolites (MFI type ZRP-5 zeolite) with various Si/A1 ratios were employed in the esterification of oleic acid with ethanol. The effect of pore size on the internal mass transfer limitation was investigated by Thiele modulus calculation. The results showed that the zeolites with high Si/Al ratios had better catalytic performance, and of these three zeolites at the same Si/A1 ratios, the ZRP-5 zeolite exhibited the lowest internal mass transfer limitations but the worst catalytic performance. Through the comparison of the Eley–Rideal model and the Langmuir–Hinshelwood model, it was indicated that on the surface of hydrophilic ZRP-5 zeolites, the adsorption of the polar ethanol molecules were more favorable than the adsorption of oleic acid molecules, resulting in less coverage of oleic acid molecules on the surface of zeolites and lower conversion rate of esterification. Moreover, the Cassie–Baxter model and the water adsorption capacity test were used to further validate the assumption of kinetic model. The highest conversion rate of 73.6% was achieved when the reaction was catalyzed by high hydrophobic Beta (50) zeolites under optimized conditions of the molar ratio of oleic acid to ethanol of 1:20, catalyst loading of 0.167 meq/g (oleic acid), temperature of 78.0 °C, reaction time of 10.0 h and stirring speed of 600 rpm. The conversion rate of oleic acid remained above 70.0% after five runs and there was no apparent loss of the active component (Al) from the zeolite.